Efficacy of Misoprostol as a Post Abortion Care - Jha, M; Chitrakar, NS; Shakya, B; Jha, R (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: This study was done to find the efficacy of Misoprostol as a post-abortion care in our setting. Methods: Women with incomplete abortion of gestational age ≤ 12 weeks or uterine size ≤ 12 weeks with open cervical os, haemoglobin ≥ 9 gm% and stable physical condition; were given 600 microgram Misoprostol orally and were observed for 24 hours for complete expulsion. If the patient failed to expel within 24 hours of Misoprostol administration manual vacuum aspiration or suction evacuation was done. Results: One hundred and twenty-two women were enrolled in the study. Among them, 41% had complete expulsion within 24 hours of administration of misoprostol and 49% had incomplete expulsions. The success rate was high in the group of < 8 weeks of pregnancy. Among 50 (41%) successful cases, 38 (76%) belonged to 8 weeks of gestation by bimanual examination (p = 0.02). Conclusions: Single dose of oral Misoprostol was effective, safe and alternative method to the management of incomplete abortion compared to the manual vacuum aspiration or suction evacuation in case of early pregnancy abortion. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 2 / Issue 16 / July-Dec, 2013 / 71-74 DOI: http://dx.doi.org/10.3126/njog.v8i2.9778